1986
DOI: 10.1677/joe.0.1100471
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical functions in a macropodid marsupial Thylogale billardierii

Abstract: In a study of adrenocortical functions in macropodid marsupials, measurements were made of the effects of ACTH infusion, ether stress and adrenaline infusion on plasma corticosteroid and glucose concentrations in wallabies (Thylogale billardierii) provided with indwelling venous catheters. The mean plasma total glucocorticoid concentration in undisturbed males and females was 80 +/- 5 (S.E.M.) micrograms/l, of which more than 90% was cortisol. This fraction declined to 68% of the total at the highest ACTH-stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…injections of cortisone acetate had no effect on the blood glucose concentration, nitrogen balance, urinary glucose excretion or the sensitivity to insulin of normal and diabetic animals (Griffiths, Mclntosh & Leckie, 1969). Other members of the Macropodidae, the quokka Setonix brachyurus (McDonald & Bradshaw, 1981), Tasmanian pademelon Thylogale biliardieri (Martin & McDonald, 1986), potoroo Potorous tridactylus and spectacled hare wallaby Lagorchestes conspicillatus (A. J. Bradley, unpublished data) also appear to be highly resistant to the diabetogenic and nitrogenmobilizing actions of glucocorticoids. On the other hand, Cooley & Janssens (1977) reported that shortterm ACTH or cortisol treatment in the tammar wallaby Macropus eugenii resulted in an increase in plasma glucose concentration, while long-term glucocorticoid treatment in this species increased both plasma glucose and nitrogen intake and output (Janssens & Hinds, 1981).…”
mentioning
confidence: 95%
“…injections of cortisone acetate had no effect on the blood glucose concentration, nitrogen balance, urinary glucose excretion or the sensitivity to insulin of normal and diabetic animals (Griffiths, Mclntosh & Leckie, 1969). Other members of the Macropodidae, the quokka Setonix brachyurus (McDonald & Bradshaw, 1981), Tasmanian pademelon Thylogale biliardieri (Martin & McDonald, 1986), potoroo Potorous tridactylus and spectacled hare wallaby Lagorchestes conspicillatus (A. J. Bradley, unpublished data) also appear to be highly resistant to the diabetogenic and nitrogenmobilizing actions of glucocorticoids. On the other hand, Cooley & Janssens (1977) reported that shortterm ACTH or cortisol treatment in the tammar wallaby Macropus eugenii resulted in an increase in plasma glucose concentration, while long-term glucocorticoid treatment in this species increased both plasma glucose and nitrogen intake and output (Janssens & Hinds, 1981).…”
mentioning
confidence: 95%